Steinbeck with Captain Tony Berry on The Western Flyer - unknown:::Creator::::::::::::
John Steinbeck with Captain Tony Berry aboard Western Flyer during the Sea of Cortez expedition. The caption on the back reads: "Steinbeck with skipper Tony Berry on the bridge of the Western Flyer during Sea of Cortez trip. Salinas Library." Magnified version of number 0-399.